Environmental Performance Of Asean - Rossazana, Ab. Rahim; Dyg Affizzah, Awang Marikan (2014)
As far as this study is concerned, there is no existing studies had measured the aggregate index of ASEAN environmental performance. The assessment of eco-efficiency performance is important as it provides sound information to the policy makers to improve the design of their environmental policies at upholding long-term sustainability of a nation. Employing data envelopment analysis (DEA) method, the results of this study reveal that smaller economies such as Laos, Cambodia and Brunei are found to be environmentally efficient. With respect to economic efficiency, larger economies such as Malaysia, Indonesia, the Philippines and Singapore are found to be more efficient than the smaller countries (except Brunei). The findings further discover that technical progress mostly explain the overall environmental performance growth while the relative efficiency changes have been minor throughout the study period of 1990 to 2008.